The strategy of manipulating conflict - Sandeep Baliga; Tomas Sjostrom (Rutgers University, Department of Economics, 2009)
Two decision-makers choose hawkish or dovish actions in a conflict game with incomplete information. The decision-making can be manipulated by extremists who send publicly observed cheap-talk messages. The power of extremists depends on the nature of the underlying conflict game. If actions are strategic complements, a hawkish extremist can increase the likelihood of conflict by sending messages which trigger a fear-spiral of hawkish actions. This reduces the welfare of both decision-makers. If actions are strategic substitutes, a dovish extremist (pacifist) can send messages which cause one decision-maker to back down and become more dovish. This reduces his welfare but benefits the other decision-maker. The hawkish extremist is unable to manipulate the decision-makers if actions are strategic substitutes, and the pacifist is equally powerless if actions are strategic complements.
Keywords: C7; 330; global strategy; Politischer Konflikt; Politische Gewalt; Signalling; Spieltheorie; Theorie